Pendanaan Dana Pensiun Program Pensiun Manfaat Pasti(Studi Kasus Dana Pensiun Universitas Muhammadiyah Surakarta) - Yudanto, Hary; , Dra. Mujiyati, M.Si (2016)
This study aims to determine how the funding conditions and the adequacy of funding owned by the Pension Fund of Muhammadiyah University of Surakarta that uses Defined Benefit Pension Plan in providing pension benefits. Determination of funding conditions and adequacy of funding based on the Ministry of Finance Decree No. 510 / KMK.06 / 2002 as well as the regulatory amendments that the Finance Minister Regulation No. 113 / PMK.05 / 2005 and Regulation of the Minister of Finance No. 21 PMK.010 / 2012. The research method used qualitative methods with objectives study a Pension Fund Muhammadiyah University of Surakarta. The primary data used in the form of Financial Statements and Reports of Actuaries. While the secondary data was the theory and the rules regarding pension funds. The results of this study indicate wealth for funding in 2013 amounting to Rp. 73,100,688,240.00 with funding ratio was 80.2%. In 2014, it has a wealth of funding of Rp. 85,561,220,873.15 with a funding ratio of 81.3%. In 2015 wealth for funding of Rp. 98,590,778,684.51 with a funding ratio of 83.8%. Muhammadiyah University of Surakarta Pension Fund should further optimize its investment with adding diversity not only through the investment of deposit and savings products in order to increase the amount of wealth for higher funding, so the impact on decreasing the amount of fees incurred by the founder. Keywords : Pension Funds, Defined Benefit Pension Plan Funding Pension Funds, Retirement Benefits, Pension Fund Investment